2014
DOI: 10.1002/stem.1587
|View full text |Cite|
|
Sign up to set email alerts
|

Nitric Oxide Controls Fat Deposition in Dystrophic Skeletal Muscle by Regulating Fibro-Adipogenic Precursor Differentiation

Abstract: Duchenne muscular dystrophy (DMD) is an hereditary disease characterized by loss of muscle fibers and their progressive substitution by fat and fibrous tissue. Mesenchymal fibro-adipogenic progenitors (FAPs) expressing the platelet-derived growth factor receptor alpha (PDGFRa) are an important source of fibrosis and adipogenesis in dystrophic skeletal muscle. Among the therapies suggested for dystrophy are those based on nitric oxide (NO) donating drugs, the administration of which slows disease progression. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 68 publications
3
74
0
Order By: Relevance
“…Other miRNAs have been shown to be important modulators of the dystrophic phenotype. For example, Cordani et al [8] recently showed that nitric oxide-induced upregulation of miR-27 was able to inhibit adipogenesis, which is an integral part of the fibrotic process.…”
Section: Mir-21 Downregulation As Anti-fibrotic Therapymentioning
confidence: 99%
“…Other miRNAs have been shown to be important modulators of the dystrophic phenotype. For example, Cordani et al [8] recently showed that nitric oxide-induced upregulation of miR-27 was able to inhibit adipogenesis, which is an integral part of the fibrotic process.…”
Section: Mir-21 Downregulation As Anti-fibrotic Therapymentioning
confidence: 99%
“…Accumulation of fat tissue is a key feature of this condition, for example, in Duchenne Muscular Dystrophy, and is believed to hinder the activity of SC. [31,32]. However, our work reveals a more direct property of ADMSC that would contribute to muscle pathology, based on our finding that they induce fibre hyper-contraction.…”
Section: Discussionmentioning
confidence: 57%
“…In the mdx mouse and DMD patients the loss of sarcolemmal nNOS results in a susceptibility to ischemia especially following mild exercise such as day-to-day limb movement. Additionally, localization of nNOS to the sarcolemma has been implicated in protection from the damaging effects of inflammation and oxidative stress, fat deposition, fibrosis and activation of satellite cells [73,229,230,231,232]. Under normal circumstances muscle derived nitric oxide (NO) attenuates the α-adrenergic vasoconstriction in exercised skeletal muscle which acts to optimize blood flow; this is referred to as functional sympatholysis [233,234,235].…”
Section: Targeting Inflammationmentioning
confidence: 99%